Chronic microplastic exposure: a growing threat to metabolic health in India - Sandhu, Manpal K.; Singla, Cheryl; Prashasti,; Oruganti, Mallikarjuna S.; Kaur, Harmehar; Kaur, Harrehmat; Sharma, Aastha; Dogra, Harry; Srijamya, (International Journal of Research in Medical Sciences, 2025)
Microplastics have emerged as widespread environmental contaminants. These particles originate from the breakdown of larger plastic waste, which is now prevalent in ecosystems, including water, soil, air, and food sources, making human exposure inevitable. If current trends continue, global plastic pollution will reach alarming levels by 2050. Microplastics primarily enter the human body via ingestion, inhalation, as well as dermal contact, along with significant exposure occurring through contaminated water, food, and urban air pollution. Various studies indicate that microplastics can disturb gut microbiota, trigger systemic inflammation, hinder lipid metabolism, and encourage issues such as insulin resistance, obesity, and cardiovascular diseases. They also serve as vehicles for toxic substances, increasing their harmful effects. This review synthesizes current evidence by searching PubMed, PubMed Central, Scopus, and Google Scholar for studies published between 2010-2025 on microplastic exposure and metabolic health, focusing on India. The scenario in India is especially concerning due to high plastic consumption, poor waste management, and a significant rate of metabolic disorders; thus, further research in this field is crucial. This review highlights the pathways of microplastic exposure to humans, along with their potential to disrupt metabolic health, emphasizing the vulnerability among the Indian population. It calls for urgent, region-specific research to explore these health risks and advocates for stricter policies on plastic waste management to mitigate the growing public health crisis.